'Mirror, mirror …': Performance and presidential politics in contemporary France. (August 2013) - Kuhn, Raymond
Performance is an integral and indispensable part of elite political behaviour in advanced democratic societies. This article analyses, explains and evaluates the practice of performance in presidential politics in contemporary France, examining how, why and to what effect presidents and 'présidentiables' perform in the mediated public sphere. It focuses particularly on the presidency of Nicolas Sarkozy and the campaign performance of the two leading candidates in the 2012 presidential election, Sarkozy and François Hollande. The article uses different data – including election results, opinion poll ratings and electoral panel studies – to support its analysis and evaluation of the particular forms of performance generated by the shifting conditions of the political communication landscape in France.